Reflexive Fieldwork in the Baram–Tinjar Region: Documenting Minority Languages - Zulkiflee, Zulfadzlee (LITPAM, 2026)
The Baram–Tinjar region of northern Sarawak is among Borneo's most linguistically diverse areas, yet it remains severely under-documented in comparative linguistics, despite sporadic scholarly attention since the mid-nineteenth century. This study explores how reflexive, ethnographically grounded fieldwork practices influence the quality, reliability, and comparative value of phonological and lexical data collected from severely underdocumented minority languages. The data presented from doctoral fieldwork conducted among minority languages in north Sarawak, including Narum, Kayan, Kiput, Miriek, Berawan, Bakong, and Tireng, documenting phonological systems, lexical inventories, and narrative data through ethnographic engagement. Framed as a comparative-historical linguistic study, the article examines fieldwork methodology, researcher positionality, relationship-building, and the social conditions of data collection as variables that directly affect data quality and historical-linguistic findings. Findings show that sustained, relationship-based fieldwork (rather than single-visit elicitation) yields more naturalistic and reliable comparative data, and that researcher reflexivity functions as a methodological control, not merely an ethical disclosure. Building on these findings, the study discusses how the resulting documentation can also support community-oriented revitalisation outputs, including pedagogical materials and local archives, as applications of documentation rather than the study's primary research aim. Overall, the study demonstrates that integrating comparative linguistics with reflexive fieldwork yields more defensible historical-linguistic data and generates practical resources for the documented communities.